Identification of Pests, Diseases, and Nutrient Deficiencies in Rice (Oriza Sativa L.) Variety Sunggal - Eva Arsitasari; Nur Rokhimah Hanik; Tri Wiharti (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
This study aims to identify pests, diseases and nutrient deficiencies in the Sunggal variety of rice (Oriza sativa L.). This research was conducted in June 2023. The research location was carried out in rice fields belonging to farmers in Sidorejo Hamlet, Polokarto District, Sukoharjo Regency. This research is descriptive qualitative by making direct observations or observations on rice fields, interviews and literature. The results showed that there were 7 pests that attacked this single variety rice plant, consisting of 5 pests from the insect class (insects), 1 from the mollusk class, and 1 from the aves class. Pests caused by insects (insects), namely: rice bug (Leptocorisa oryzae), ground bed bug (Scotinophara coarctata), white rice stem borer (Scirpophaga innotata Walker), armyworm (Spodoptera litura), grasshopper (Oxya servile). Caused by molluscs, namely the golden snail (Pomacea canaliculate) and caused by birds, namely sparrows (Lonchura sp). While there are 6 caused by diseases, namely caused by fungi/fungi there are 5 and caused by bacteria there is 1. Among those caused by fungi/fungus namely: brown leaf spot on rice (Helminthosporium oryzae), narrow brown leaf spot on rice (Cercospora oryzae), stem rot in rice (Sclerottium oryzae), rice leaf blight (Rhizotonia solani) and leaf blast (Pyricularia grisea). Caused by bacteria, namely bacterial leaf blight of rice (bacteria: Xanthomonas oryzae pv oryzae). Then lastly there is one that is caused by a lack of nutrients, namely: potassium deficiency.